Finite element analysis of cohesive element for glass epoxy composite fuselage model - Ng, Wei Sim (2011)
In this research, a numerical simulation on a newly introduced fabrication miniature composite fuselage structure - a glass epoxy composite laminated with adhesively bonded butt joint under axial compression loading is presented. A FEA via ABAQUS/Explicit is utilized to capture the complete compressive response to predict the crushing behaviour and mechanical strength from initial compression loading up to the final failure is demonstrated. A woven C-glass fiber/epoxy 200 g/m2 composite laminated with the orthotropic elastic material properties is modeled as continuum composite lay-up in the proposed numerical model. The adhesively bonded joint progression is modeled using cohesive elements technology that allows the correct accounting for the energy involved in the crushing process and investigates the capability of the bonded joint to withstand the axial crushing impact from debonding failure. An experiment of Double Cantilever Beam (DCB) according to the ASTM Standard D5528 is performed to determine the adhesive Mode I critical toughness. The crushing load and collapse modes under axial compression loading from FEA results indicate good correlation with the experimental test. The discrepancy of the peak load is found to be at 1%.